Theory of Rights in Islamic Economic Law and Its Relation to Intellectual Property Rights - Asari, Aang; Pradhana, Theo Aditya; Averro, Muhammad Faruq; Firdaus, Muhammad Irkham (AL-IKTISAB: Journal of Islamic Economic Law, 2022)
â€¢â€¢â€¢ English â€¢â€¢â€¢ The study of the theory of rights in Islamic economic law and its relation to intellectual property rights is an outpouring of ideas from the author. That in this research, although the term Intellectual Property Rights (IPR) is not known in the turats books, basically this is part of the theory of rights in fiqh muamalah, namely haq al-ibtikar. Haq al-ibtikar is an extraordinary privilege for a creation that was first created by a scientist through his way of thinking or his analysis as outlined in a work. For example, such as writing, books, videos, or other media. The research method used in this article is a qualitative approach, which is done by researching library materials which are secondary data and then described based on the analysis of the data. The results of this research are that copyright is legally protected from an Islamic point of view, and copyright infringement is seen as a violation of property or assets, so the legal sanctions are the same as sanctions for theft of property or property belonging to others. However, it should be emphasized that in Islam only recognizes and protects copyrighted works that are in harmony with the norms and values contained in them. If the copyrighted work is contrary to Islamic values, then it is not recognized as a copyrighted work, even protection for copyrighted works does not even exist and is not legal to protect. In Indonesia, the rules regarding haq al-ibtikar are regulated in UU No. 28/2014 concerning Copyright. â€¢â€¢â€¢ Indonesian â€¢â€¢â€¢ Kajian tentang teori hak dalam hukum ekonomi syariah serta kaitannya dengan hak kekayaan intelektual merupakan sebuah curahan dan gagasan pemikiran dari penulis. Bahwasannya dalam kajian ini, walaupun istilah Hak Kekayaan Intelektual (HKI) tidak dikenal dalam kitab-kitab turats, pada dasarnya ini merupakan bagian dari teori hak yang ada dalam fiqh muamalah, yaitu haq al-ibtikar. Haq al-ibtikar adalahÂ suatu keistimewaan yang luar biasa atas suatu ciptaan yang pertama kali dibuat yang dihasilkan oleh seorang ilmuan melalui jalan pemikirannya atau analisisinya yang dituangkan dalam suatu karya. Misalnya seperti tulisan, buku, video, atau media lainnya. Metode penelitian yang digunakan dalam artikel ini adalah dengan pendekatan kualitatif, yang dilakukan dengan cara meneliti bahan pustaka yang merupakan data sekunder lalu kemudian dideskripsikan berdasarkan analisis data tersebut. Hasil dari kajian ini adalah secara hukum hak cipta dalam sudut pandang Islam dilindungi keberadaannya, dan pelanggaran terhadap hak cipta dipandang sebagai pelanggaran terhadap properti atau harta kekayaan, sehingga sanksi hukumnya sama seperti halnya sanksi terhdap pencurianÂ harta atau benda milik orang lain. Namun perlu dipertegas bahwasannya dalam Islam hanya mengakui dan melindungi karya cipta yang selaras dengan norma dan nilai yang ada di dalamnya. Jika karya cipta tersebut bertentangan dengan nilai-nilai Islam, maka ia tidak diakui sebagai karya cipta, bahkan perlindungan terhadap karya cipta pun tidak ada bahkan tidak sah untuk dilindungi. Di Indoensia aturan tentang haq al-ibtikar di atur dalam UU No. 28/2014 tentang Hak Cipta.